112-Gb/s DSP-Based PAM-4 Transceivers for Large-Scale Ethernet Switching Systems - Henry Park; Mohammed Abdullatif; Ehung Chen; Tamer Ali (IEEE Open Journal of the Solid-State Circuits Society)
As modern ASICs integrate several hundred interconnect ports in a large package, ASIC Serdes design faces challenging performance, power, and area targets. Thanks to architectural advancements and technology scaling, a DSP-based transceiver has demonstrated better than 40-dB loss compensation with competitive power and area that enabled very large-scale Serdes integration in a single package. This article reviews two recent publications for long-reach ASIC Serdes designed in 5- and 7-nm FinFET. With detailed discussions on design challenges from major building blocks, TX/RX/PLL, a novel TX data path bandwidth extension technique by a feedback equalizer is proposed with silicon data.